Methodological reflections on the use of systematic reviews in early childhood research. (March 2018) - Ang, Lynn
This article sets out to look critically at the use of systematic reviews in the cross-disciplinary field of early childhood and international development. Systematic reviews – a specialist methodology involving the secondary analysis of existing knowledge on a particular topic – is prevalently used to address complex questions in social and health-related policy and is an established tradition in the life and health sciences. In education and the social sciences, there is burgeoning interest in systematic methodological approaches, although its usage remains comparatively lagging compared to the medical field. Drawing on an interdisciplinary systematic review of empirical research on early childhood development and peacebuilding in the Asia Pacific region, this article reflects on the use of the methodology and its potential to inform new conceptual and methodological developments. The article argues that our knowledge of children and the early years can be significantly advanced by furthering debates on systematic reviews particularly in cross-disciplinary fields and its application, as well as relevance for how evidence is evaluated and applied. This is especially pertinent in a sector driven by increasing calls for more reliable and timely information to influence practice and policy decision-making.